Understanding the Impact of Seeing Gun Violence and Hearing Gunshots in Public Places: Findings From the Youth Firearm Risk and Safety Study. Issue 17 (September 2021) - Mitchell, Kimberly J.; Jones, Lisa M.; Turner, Heather A.; Beseler, Cheryl L.; Hamby, Sherry; Wade, Roy
There is a current public health emphasis on finding strategies for reducing the risks associated with children's gun violence exposure. This article examines the impact of seeing and hearing gun violence on youth of different ages and living in urban and nonurban areas. Participants were 630 youth, aged 2 to 17. Youth, ages 10 to 17, completed a self-report survey, and caregivers of young children, ages 2 to 9, completed the survey as a proxy for that child. Participants resided in Boston, MA; Philadelphia, PA; and rural areas of eastern TN. Participants were recruited through a variety of techniques including pediatric clinics, housing authorities, youth-serving agencies, festivals, word of mouth, and local e-mail lists for classified advertisements. Data were collected between October 2017 and April 2018 and analyzed in 2019. In total, 41% of youth in this study reported ever seeing or hearing gun violence; 32% had such an experience in the past year. Among exposed youth, 50% took protective action to keep themselves safe, and 58% reported being very or extremely afraid, sad, or upset as a result of the indirect gun violence. More youth living in urban compared with nonurban areas took some protective action. Females and younger children had increased odds of experiencing high fear as a result of the violence. Current gun violence prevention has typically targeted adolescents; however, current findings suggest the need to focus on younger children as well, including the distress resulting from indirect exposure to gun violence.